2018
DOI: 10.1115/1.4041236
|View full text |Cite
|
Sign up to set email alerts
|

Neimark-Sacker Bifurcations Near Degenerate Grazing Point in a Two Degree-of-Freedom Impact Oscillator

Abstract: Saddle-node or period-doubling bifurcations of the near-grazing impact periodic motions have been extensively studied in the impact oscillators, but the near-grazing Neimark-Sacker bifurcations have not been discussed yet. For the first time, this paper uncovers the novel dynamic behavior of Neimark-Sacker bifurcations, which can appear in a small neighborhood of the degenerate grazing point in a two degree-of-freedom impact oscillator. The higher order discontinuity mapping technique is used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Up to now, most of the studies on SNAs has been confined to smooth dynamic systems. The nonsmooth systems have abundant nontypical dynamics [28,29]. It has been found that SNAs can also be generated in the nonsmooth system in several past works [30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most of the studies on SNAs has been confined to smooth dynamic systems. The nonsmooth systems have abundant nontypical dynamics [28,29]. It has been found that SNAs can also be generated in the nonsmooth system in several past works [30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…As a special bifurcation of nonsmooth systems, the grazing bifurcation is a qualitative transition between impact and nonimpact motion [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Nordmark [31,32] studied the dynamic behavior near the grazing trajectory and a nonlinear mapping is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…e existence condition and stability of the grazing periodic orbit are derived in a two degree-of-freedom vibroimpact system with one-sided constraint in [36]. Yin et al [37][38][39][40][41][42] analyzed and measured the degenerate grazing bifurcations of the impact systems.…”
Section: Introductionmentioning
confidence: 99%